EFFECTS OF CARICA PAPAPYA SEED EXTRACT ON HISTOPATHOLOGICAL CHANGES IN AMINOGLYCOSIDE-TRIGGERED ACUTE NEPHROTOXICITY IN EXPERIMENTAL RATS - Ahmad, Sameer; Khan, Sher Afghan; Tayyab, Mehwish; Arain, Abdul Qudoos; Ali, Amanat; Khalil, Hafsa (Pakistan Journal of Physiology, 2024)
Background: Nephrotoxicity is an emerging complication arising with the use of multiple drugs and dietary modifications. The objective of this study was to determine the nephroprotective effect of aqueous extract of Carica papaya seeds in aminoglycoside induced acute nephrotoxicity in rats. Methods: This Quasi Experimental study was conducted on 30 Sprague Dawley rats. After nephrotoxicity was confirmed by measuring serum urea and creatinine levels histomorphological examination of kidney tissue was done. Results: Group A, Group C and Group B had a mean serum urea level of 24.70±1.633, 82.70±2.587 and 81.00±1.247 mg/dL respectively (p<0.05), showing nephrotoxicity on day 6. On day 11, mean blood urea level for Group C was 50.60±1.857 mg/dL (p<0.05) compared to Group B with mean blood urea level 78.60±1.240. The reduced mean blood urea levels of Group C in comparison to Group B indicated nephroprotection from aqueous extract of Carica papaya seeds. In Group A, Group B and Group C the mean serum creatinine level was 0.750±0.619, 1.980±0.467 and 2.030±0.667 mg/dL (p<0.05) respectively, on day 6 indicating nephrotoxicity with Gentamycin. Group B had mean serum creatinine levels of 1.920±0.0389 at day 11 while Group C had a mean serum creatinine of 1.380±0.611 after 5 days of therapy with Carica papaya seed aqueous extract on day 11 indicating nephroprotection. Conclusion: Aqueous extract of Carica papaya seeds has significant nephroprotective effects on aminoglycoside induced acute nephrotoxicity. Pak J Physiol 2024;20(3):3?7 DOI: https://doi.org/10.69656/pjp.v20i3.1637